Pengaruh Anggaran Biaya Produksi Terhadap Peningkatan Pendapatan Pada PT. Perkebunan Nusantara II (Persero) Kebun Melati Perbaungan - Benny Jh Pardede; Warsani Purnama Sari; Yusnaini Yusnaini; Isnaniah LKS (Economics, Business and Management Science Journal, 2022)
This research aims to determine the influence of budget production costs to increase revenue at PT. Plantations of Nusantara II (Persero) Plantation Jasmine Perbaungan. The type of research used is associative research. The population used in this research is the income statement of PT. Plantations of Nusantara II (Persero) Plantation Jasmine Perbaungan. The sample used is the income statement for the period 2015-2018. The type of data used in this study is the quantifying data, while the data source used is secondary data. The data collection techniques used are documentation. The data analysis technique is with the quantifying tenics. With a simple linear regression method with the help of Statistical Package For Social Sciences (SPSS) 21. The results of this study showed that the production cost variables did not affect the increase in revenue at PT. Plantation Nusantara II (Persero) Kebun Melati period 2015-2018.